FAKTOR-FAKTOR YANG MEMPENGARUHI PENATALAKSANAAN INISIASI MENYUSU DINI DI RSUD SYEKH YUSUF KABUPATEN GOWA - Muhammad Fakhruddin (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2020)
Research Objectives: to determine the factors that influence the management of Early Breastfeeding Initiation in RSUD Syekh Yusuf Gowa District. Method: The design of this study was Cross Sectional Study, the sample in this study were all mothers as many as 32 people. The data used are primary data and sampling technique that is purposive sampling, Result: based on statistical test result by using chi square = X² it can be concluded that there is relation between knowledge with IMD management p = 0,00, family support with management of IMD p = 0.015, and no attitude relationship with the management of IMD p = 0,492, Discussion: support of husband and family very important role in implementing IMD. In the implementation of IMD the father or family is advised to assist at the time of delivery and after childbirth. Conclusion: there is a meaningful relationship between knowledge, family support and no significant relationship attitudes with the management of IMD